2010
DOI: 10.1093/jaoac/93.4.1137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Salazinic, Norstictic, and Usnic Acids in Xanthoparmelia chlorochroa by Ultra-Performance Liquid Chromatography/Tandem Mass Spectrometry

Abstract: The lichen species Xanthoparmelia chlorochroa is toxic when consumed by domestic sheep, cattle, and Rocky Mountain elk. Clinical signs exhibited by poisoned animals include red urine, ataxia, and muscular weakness that rapidly progresses to recumbency. Elk are unable to recover once becoming recumbent; however, most affected cattle can recover if offered suitable feed shortly following the onset of signs. At present, the pathogenesis and specific toxin(s) are unknown. As part of an effort to elucidate the prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The four independent variables, including the camphor:thymol (X1) molar ratio, the Although the solubility of UA in acetone (see Table 1) allowed exhaustive extraction from the raw material (1.45 mg of UA from 100 mg of raw material with a UA solubility of about 9.55 mg/1.5 mL of acetone), the extraction yield was relatively low, and the subsequent extraction steps increased the yield only slightly. This phenomenon showed that, although acetone is the most common solvent used for the extraction of lichen metabolites [5,10,[14][15][16][17][18][19][20], this extractant did not provide exhaustive extraction of UA from C. uncialis.…”
Section: Polynomial Regression Modes Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The four independent variables, including the camphor:thymol (X1) molar ratio, the Although the solubility of UA in acetone (see Table 1) allowed exhaustive extraction from the raw material (1.45 mg of UA from 100 mg of raw material with a UA solubility of about 9.55 mg/1.5 mL of acetone), the extraction yield was relatively low, and the subsequent extraction steps increased the yield only slightly. This phenomenon showed that, although acetone is the most common solvent used for the extraction of lichen metabolites [5,10,[14][15][16][17][18][19][20], this extractant did not provide exhaustive extraction of UA from C. uncialis.…”
Section: Polynomial Regression Modes Developmentmentioning
confidence: 99%
“…Usnic acid (UA) is a phenolic compound with a dibenzofuran structure occurring in the form of two enantiomers ( Figure 1 ) [ 1 ] in several lichen genera ( Alectoria , Cladonia , Evernia , Lecanora , Parmelia , Ramalina , Usnea , and Xanthoparmelia ) as a yellow cortical pigment [ 2 , 3 , 4 , 5 , 6 ]. Nowadays, it is the most extensively investigated lichen secondary metabolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Some of these show antioxidant [24] and cancer-chemopreventive activity, [25] as well as UV screening capacity, [26] defence functions against herbivores [27] and toxic effects to domestic and wild mammals. [28] Crude extracts from X. chlorochroa (TUCKERMAN) HALE exhibited antiproliferative effects against lymphoma (Rajii) cells. [19] Although Xanthoparmelia lichen thalli may thus appear a promising source of natural products, they may also pose difficulties and limitations for the collection of homogeneous materials in bulk quantities to test and exploit LSMs [22] : the high LSMs availability lies within a complex framework of variability, which is still widely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Lichens of the world‐wide distributed genus Xanthoparmelia ( Vainio ) Hale are known to synthesize more than 90 LSMs . Some of these show antioxidant and cancer‐chemopreventive activity, as well as UV screening capacity, defence functions against herbivores and toxic effects to domestic and wild mammals . Crude extracts from X .…”
Section: Introductionmentioning
confidence: 99%